Formal language assessment in low-educated persons with aphasia: can the lesion effect be distinguished from the education effect? - MEDEIROS, Natalia Malagueta de; ORTIZ, Karin Zazo (Arquivos de Neuro-Psiquiatria, 2022)
Background: Language tests are important in the assessment and follow up of people with aphasia (PWA). However, language assessment in the low literacy population is still a challenge. Objective: To investigate whether a formal evaluation of aphasia is able to distinguish the neurological effect from the effect of low educational level in people with post-stroke aphasia. Methods: The sample consisted of a group of 30 aphasic subjects (AG) and a control group (CG) of 36 individuals, both with an educational level of 1-4 years. The Brazilian Montreal-Toulouse Language Assessment battery was applied to all subjects. Results: There were statistically significant differences between the groups in 19 out of the 20 tasks analyzed. Conclusions: These results suggest that formal evaluation procedures are able to detect language disorders resulting from stroke, even in subjects with low educational level.
Keywords: Aphasia; Language; Education